Assessment of noise pollution in sports halls in Lahijan, Iran - Maryam Hajesmaeiliyan; Ali Fahimi Nezhad; Bagher Morsal (Anthropogenic Pollution)
The aim of this study was to assess the noise pollution of sports facilities in multi-purpose halls in Lahijan city, Iran. This research was of applied type. Through networking, 16 halls were randomly selected in four zones of the city and data were collected in the field. The sound level in the clubs was measured at level A and as an equivalent level by a portable device and Decibel X 2019 and compared with the sound standard (OSHA-90 dBA). The measurements were performed in triplicate and repeated three times. The calculated parameters included sound pressure level (SPL), average sound level ((LP) ̅), continuous sound equivalent level (Leq) and individual daily dose LAEp,d. The results showed that the lowest sound pressure level was 73.9 dB in the northern zone and in the first turn. The highest sound pressure level in the western zone was 97.7 dB. As the time changed from early morning to night, the average sound pressure level increased, highlighting the direct relationship between the sound pressure level and the measurement time. The average sound level in the western zone was higher than in other zones, and the average sound level in the southern zone was lower than in other zones. In both zones, the gyms were of the shed type, which could not establish a relationship between the structural form and the sound level. All the studied halls had levels higher than the standards for recreation centers and parks, as well as the standards of the United States Environmental Protection Agency (EPA). However, all of the gyms met other standards such as ACGIH, NIOSH and OSHA standards related to occupational health. Finally, there was a relationship between the urban location of sports halls and the sound level, such that halls located in the northern and western zones (the more affluent part of the city) had higher sound levels; in contrast, those located in the southern and eastern zones (poorer areas of the city) had lower sound levels.